MODEL-MODEL TANGGUNG JAWAB SOSIAL DAN ASPEK PERPAJAKANNYA - Irawan, Ronny (Widya Mandala Surabaya Catholic University, 2009)
Corporate social responsibility is contm-service of company to its environment and society since company already has gains from them. There are various models of corporate social responsibility carried alit by the companies in Indonesia. They can involve directly to pelform the events of responsibility or through third party. They can also make a cooperation with another par(y or join to another party. They can give contributions to the people and their er. vironment directly by increasing their quality of life. But, they have to obey the rules and regulations set by government for their sustainability. The different types of s;)cial re5ponsibility programs need different treatments of their taxation.